Sulindac sulfide selectively increases sensitivity of ABCC1 expressing tumor cells to doxorubicin and glutathione depletion - Whitt, Jason D. (J Biomed Res, 2016)
ATP-binding cassette (ABC) transpo rters ABCC1 (MRP1), ABCB1 (P-gp), and ABCG2 (BCRP) contribute to chemotherapy failure. The primary goals of this study were to characterize the efficacy and mechanism of the nonsteroidal anti-inflammatory drug (NSAID), sulindac sulfide, to reverse ABCC1 mediated resistance to chemotherapeutic drugs and to determine if sulindac sulfide can influence sensitivity to chemotherapeutic drugs independently of drug efflux. Cytotoxicity assays were performed to measure resistance of ABC-expressing cell lines to doxorubicin and other chemotherapeutic drugs. NSAIDs were tested for the ability to restore sensitivity to resistance selected tumor cell lines, as well as a large panel of standard tumor cell lines. Other experiments characterized the mechanism by which sulindac sulfide inhibits ABCC1 substrate and co-substrate (GSH) transport in isolated membrane vesicles and intact cells. Selective reversal of multi-drug resistance (MDR), decreased efflux of doxorubicin, and fluorescent substrates were demonstrated by sulindac sulfide and a related NSAID, indomethacin, in resistance selected and engineered cell lines expressing ABCC1, but not ABCB1 or ABCG2. Sulindac sulfide also inhibited transport of leukotriene C(4) into membrane vesicles. Sulindac sulfide enhanced the sensitivity to doxorubicin in 24 of 47 tumor cell lines, including all melanoma lines tested (7-7). Sulindac sulfide also decreased intracellular GSH in ABCC1 expressing cells, while the glutathione synthesis inhibitor, BSO, selectively increased sensitivity to sulindac sulfide induced cytotoxicity. Sulindac sulfide potently and selectively reverses ABCC1-mediated MDR at clinically achievable concentrations. ABCC1 expressing tumors may be highly sensitive to the direct cytotoxicity of sulindac sulfide, and in combination with chemotherapeutic drugs that induce oxidative stress.